Cytological techniques to analyze meiosis in Arabidopsis arenosa for investigating adaptation to polyploidy - Higgins, James D.; Wright, Kevin M.; Bomblies, Kirsten; Franklin, Chris (Frontiers in Plant Science, 2014)
Arabidopsis arenosa is a close relative of the model plant Arabidopsis thaliana, and exists in nature as stable diploid and autotetraploid populations. Natural tetraploids have adapted to whole genome duplication and do not commonly show meiotic errors such as multivalent and univalent formation, which can lead to chromosome non-disjunction and reduced fertility. A genome scan for genes strongly differentiated between diploid and autotetraploid A. arenosa identified a subset of meiotic genes that may be responsible for adaptation to polyploid meiosis. To investigate the mechanisms by which A. arenosa adapted to its polyploid state, and the functionality of the identified potentially adaptive polymorphisms, a thorough cytological analysis is required. Therefore, in this chapter we describe methods and techniques to analyze male meiosis in A. arenosa, including optimum plant growth conditions, and immunocytological and cytological approaches developed with the specific purpose of understanding meiotic adaptation in an autotetraploid. In addition we present a meiotic cytological atlas to be used as a reference for particular stages and discuss observations arising from a comparison of meiosis between diploid and autotetraploid A. arenosa.